2010
DOI: 10.1002/cncr.24958
|View full text |Cite|
|
Sign up to set email alerts
|

Alemtuzumab by continuous intravenous infusion followed by subcutaneous injection plus rituximab in the treatment of patients with chronic lymphocytic leukemia recurrence

Abstract: Background Monoclonal antibodies may be used more effectively in combination. A previous study of intravenous (iv) bolus alemtuzumab plus rituximab in patients with chronic lymphocytic leukemia (CLL) recurrence produced a response rate of 54% after a 4-week treatment period. Methods To optimize dose, schedule, and route of alemtuzumab, a study was designed exploring continuous intravenous infusion (civ) followed by subcutaneous (sc) alemtuzumab together with weekly iv rituximab in patients with previously tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…Nonchemotherapy regimens such as alemtuzumab-rituximab, [93][94][95] lenalidomide monotherapy, 96 lenalidomide in combination with rituximab, 97 rituximab monotherapy, 98 rituximab-GM-CSF, 99 and high-dose methylprednisolone Ϯ rituximab 100 have also been explored in clinical trials. With the exception of the alemtuzumabrituximab regimen for patients with nonbulky disease and/or del(17p13) and the methylprednisolone-rituximab regimen, there are currently inadequate data to recommend the routine use of these regimens.…”
Section: When Should Elderly Patients Be Treated?mentioning
confidence: 99%
“…Nonchemotherapy regimens such as alemtuzumab-rituximab, [93][94][95] lenalidomide monotherapy, 96 lenalidomide in combination with rituximab, 97 rituximab monotherapy, 98 rituximab-GM-CSF, 99 and high-dose methylprednisolone Ϯ rituximab 100 have also been explored in clinical trials. With the exception of the alemtuzumabrituximab regimen for patients with nonbulky disease and/or del(17p13) and the methylprednisolone-rituximab regimen, there are currently inadequate data to recommend the routine use of these regimens.…”
Section: When Should Elderly Patients Be Treated?mentioning
confidence: 99%
“…Phase 1/2 studies in hematological malignancies with rituximab in combination with either epratuzumab, galiximab or alemtuzumab, which target the B-cell antigens CD22, CD80 and CD52, respectively, demonstrated that these combinations were well-tolerated and resulted in clinical responses equal to or greater than single-agent therapy alone ( Table 2). [168][169][170][171] Preclinical evidence for expanded hematological indications for the combination of anti-CD20 and anti-CD52 mAbs have been reported and may influence further development of this combination, 172,173 although issues with adventitious infections may complicate its use as consolidation therapy. 174,175 A Phase 2b study testing the combination of rituximab and lumiliximab, which targets the B-cell marker CD23, did not achieve clinical superiority even though there were favorable signals in earlier trials.…”
Section: Immunomodulatory Mab Combinationsmentioning
confidence: 99%
“…The most adverse events were again infusion-related and well manageable. Infections were seen in 28 % of the patients; 15 % of the patients developed CMF infections which were only detected in blood samples without organ manifestation [16].…”
Section: Alemtuzumabmentioning
confidence: 99%